Characterization and Variability Studies of the Local Small Size Potato (Solanum sp.) Genotypes under Sub-Himalayan Foothills of India - Chowdhury, Riman Saha; Datta, Suchand (International Journal of Bio-resource and Stress Management, 2020)
An experiment was conducted with twenty five small size potato (Solanum sp.) genotypes to characterize the different growth, yield and quality characters as well as its variability. The research work was conducted at the Instructional farm of the Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, and West Bengal, India during the year 2017-18 and 2018-19. The experiment was laid out in randomized block design with tree replications The genotypes were characterized for 37 characters namely, tuber characters, sprout and stem characters, leaf characters and growth habit. These genotypes upon sorting showed discrete variation with respect to vegetative, tuber and quality characters. Wide range of variation was also pragmatic among the genotypes for quite a few morphological, tuber and quality characters. Among the different tuber characters absence of secondary tuber colour, shallow depth of tuber, intermediate note of eyes per tuber, evenly distributed eye showed 100% frequency and other leaf and growth characters also shows higher frequency. Variability studies were bare that there was an extensive range of inconsistency for all the characters studied. High GCV and PCV were found in case of anthocyanin content of tuber and yield of tuber plant-1. High heritability along with high genetic advance (as percentage of mean) was found in tuber yield plant-1 and average weight of single tuber. These characters may be painstaking as trustworthy selection indices as they are possibly governed by additive gene effect.